Digital Capability and Literacy for MSME Transformation: Perspectives of Digital and Business Performance - Wulandari, Astri; Marcelino, Dandy; Suryawardani, Bethani; Adithya, Donny (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
The presence of MSMEs (Micro, Small, and Medium Enterprises) in Indonesia plays a crucial role in driving the Indonesian economy, particularly at the grassroots level. However, the adoption of information technology and digitalization within MSMEs often lacks strategic methods, such as financial analysis or forecasting. MSMEs tend to approach emerging technology solutions with caution. To help MSMEs better understand the advantages of adopting digital transformation, it is essential to evaluate the performance of their digitalization efforts. This study aims to explore how MSMEs in Indonesia can sustain and grow in the digital era by implementing digital business strategies, focusing on digital capabilities and literacy, and examining their influence on perceived business performance. Data collection was conducted through an online survey over six months, from July 2022 to January 2023, targeting 400 MSME respondents across Indonesia. Hypothesis testing was performed using Structural Equation Modeling (SEM) using SmartPLS The findings indicate that digitalization capabilities, on their own, do not have a direct, significant positive impact on perceived business performance. However, when mediated by digitalization performance, these capabilities show a significant and positive effect on perceived business outcomes. Results indicate that the influence of digitalization capabilities and literacy on digitalization performance and perceived business performance ranges from moderate to strong. Additionally, the findings reveal that MSME actors do not yet prioritize perceived business performance in digitalization, as digitalization is still viewed as an additional expense. Therefore, stronger digital literacy is needed regarding the more measurable results of digitalization implementation.